Developing Confidence, Developing Skills: The Perceived Effect of Professional Development on Online Teaching - Hill, Michael; Hart, Cassandra; Baker, Rachel; Xu, Di; Alonso, Emily; Nguyen, Alyssa; d'Arcy, Kim; Bailey, Cheryl; VanNorman, Tim; Nguyen, Vivian; Pakula, Jennifer (Online Learning, 2025)
A large body of research has documented weaker student performance in online courses relative to face-to-face courses across multiple outcomes, including grades, course completion, and persistence. These gaps are particularly pronounced for underserved students. In response, colleges and universities have sought to improve the quality of online instruction by providing technology resources, student and faculty technical support, and, the focus of this study, professional development for faculty teaching online. However, despite the increasing popularity of professional development for online instructors, evidence on its effectiveness in shaping faculty practices and confidence remains limited. This study used survey data from 82 faculty at two Southern California community colleges following participation in structured professional development programs designed to improve online teaching. The professional development programs focused on core learning theories and practical strategies for engaging virtual learners. We find that the majority of faculty reported adopting techniques related to the creation of a supportive and welcoming environment, recorded video introductions and lectures, and increased student-student interaction. In addition, instructors reported increased confidence in adopting teaching methods in almost all assessed areas. In technical areas, most respondents reported increased confidence in skills related to building an online course, creating online assignments and materials, and interacting with students. In soft skill areas, most respondents reported increased confidence in skills related to development of a welcoming, equitable online environment. These survey results underscore the critical role of professional development in shaping instructors’ online teaching confidence and practices.